The Fado Museum: Heritage Infrastructure or Tourist Attraction? - Salwa El-Shawan Castelo-Branco; Iñigo Sánchez-Fuarros (Via@)
This article explores Lisbon’s Fado Museum as an affective, material, symbolic, and performative site of memory in which different audiences such as tourists and the local fado community converge, without necessarily intersecting. We argue that the Fado Museum has evolved from a mere exhibiting space to become a multivalent “heritage infrastructure” that facilitates new spaces of agency in which novel forms of relating to —and dwelling in— heritage emerge. By recognizing the importance of the Fado Museum in the institutionalization and legimitization of fado as city heritage —and its significance to the social and symbolic production of Alfama as a fado neighborhood—, we ultimately aim to problematize the function of this kind of heritage infrastructures in the complex relationship between tourism, heritagization, and urban regeneration in the era of overtourism.